Approach to biomimetic design. learning and application (2014)
Learning biomimetic design methods can be difficult and involve a long period of time, previous experiences have shown that the application of biomimetics in industrial design and product development projects requires an adaptation to traditional methods through a simpler model and a learning system. There are various biomimetic design processes, adaptation, integration and application corresponds to objectives of each project. A learning method for the application of biomimetics in design projects, step by step or globally, is presented. The knowledge of biological principles and translating them into engineering principles underlie each method, learning is augmented by adding methods based on creativity and functional analysis to achieve innovative products thanks to a biomimetic approach.